ANALISIS PERBEDAAN PEMBELIAN IMPULSIF DITINJAU DARI GENDER KONSUMEN PADA PUNCAK TOSERBA BENGKULU - Ida Anggriani; Fera Indasari (UNIVED Press, 2018)
Ida Anggriani, Fera Indasari; The purpose of this study was to the differences in terms of impulsive buying gender determine consumers at Puncak Toserba Bengkulu. This type of research is a comparative study, carried out to compare the similarities and differences of two or more of the facts and object properties in the framework based on certain carefully. Survey respondents as many as 100 people composed of 50 men and 50 women, samples were taken by purposive random sampling technique. Data collection using questionnaire and analysis methods by means of descriptive and quantitative analyzes using independent samples t test trials. Results of this study indicate that there are differences between the purchase impulsive significant gender beetween men and women at Puncak Toserba Bengkulu by comparison Tsig (0,047) <α (0,05). The average difference for the two groups were between to 1,520 ranged 0,019 until 3,021.Keywords: Impulsive Buying, Gender